Investigation of dynamics properties of dissimilar materials produced by friction stir welding - Siti Norazila, Zahari (2017)
The finite element (FE) model is broadly used in predicting the overall response of a complex structure with the requirement of highly computational effort. In order to reduce computational problem, FE model tends to be developed by reducing the details using certain assumptions or model simplification by neglecting the local features such as joint. Unfortunately, these developments will result to the inaccuracy of FE model mainly due to some errors introduced during the construction of FE model. Therefore, the development of an accurate FE model of local features becomes more significant for predictions of dynamic behaviours of complex structure with joint and also for further analysis. This study will be focused on the configuration errors, which are the „key‟ features in structure known as joints modelling which significantly influence dynamic properties of the model. Friction stir welding (FSW) with butt joint configuration joints structure was chosen in this project due to its ability to join similar and dissimilar materials and its growing application in the industries. There are two main stages involved in completing the study; selection of ideal specimen of FSW and reliable joint modelling strategies for FSW structure. For the first stage, nine specimens of specimens containing series of aluminium alloy; AA7075 and AA6061 were fabricated using various types of FSW welding parameters. In order to find the most optimum specimen of FSW plate, the finite element model using equivalence technique was developed and normal mode analysis in MSC Nastran/Patran (SOL 103) was performed to extract the modal parameters (natural frequency and mode shapes). Then, the correlation between FEA and EMA results provided was made and the ideal specimen was chosen. The second stage was started by constructing three types of joint modelling in FE model of FSW structure. Connecting elements that were engaged in this study are rigid body element Type 2 (RBE2), bar element (CBAR) and spot weld element connector (CWELD). SOL 103 was performed on the three models and correlation between prediction modal data and test results for the ideal specimen chosen in the first stage (specimen E) was made. Based on the results obtained, it demonstrates that CWELD element showed lower percentage of error which is 5.13 % compared to the other two elements. CWELD elements were chosen to represent weld model for FSW joints due to its accurate prediction of mode shapes besides containing an updating parameter for weld modelling compared to other weld modelling. After model updating was performed, it was also concluded that the most sensitive updating parameters are E7075, followed by E6061 and ʋ7075. In performing the model updating by using these selected updating parameters, the average error of the natural frequencies for CWELD model reduced to 4.47 % which is 0.66% lower than before performing the model updating.